2001
DOI: 10.1038/sj.gt.3301489
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of the herpes simplex thymidine kinase gene in a replicating adenovirus does not augment antitumor efficacy

Abstract: Replication-incompetent adenoviruses (Ad) carrying the herpes simplex thymidine kinase (HSVtk) gene have been used in a number of human cancer gene therapy trials, however transduction has generally been limited to a small minority of tumor cells. To solve this problem, replication-competent adenoviral vectors carrying transgenes such as HSVtk have been developed. However, contradictory evidence exists regarding the efficacy of these new vectors. Accordingly, we constructed and tested a replication-competent E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…Overexpression of the death protein, expression of TRAIL or deletion of the E1b-19kD gene, all have been shown to improve viral spread and efficacy of replicating adenoviruses in vitro and in vivo. 20,35,43,52,53 Various suicide genes [54][55][56][57][58] or TNF-a [59][60][61] have also been expressed with replication-competent vectors to improve cell killing, although with mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the death protein, expression of TRAIL or deletion of the E1b-19kD gene, all have been shown to improve viral spread and efficacy of replicating adenoviruses in vitro and in vivo. 20,35,43,52,53 Various suicide genes [54][55][56][57][58] or TNF-a [59][60][61] have also been expressed with replication-competent vectors to improve cell killing, although with mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that the antitumor efficacy of HSV-TKexpressing oncolytic adenoviruses is augmented by GCV treatment [19][20][21] . On the contrary, other studies have suggested that GCV does not further improve the oncolytic potential of replicating adenoviruses, at least not in vivo [22][23][24][25] . The studies by Raki et al and Wilder et al did not assess whether any differences existed in the tumor weight between the groups.…”
Section: Discussionmentioning
confidence: 85%
“…We presume that the oncolytic effect could not counteract the rapid increase in the number of tumor cells when the tumor volume was >100 mm 3 . Third, in the study by Lambright et al [25] , the time of tumor exposure to oncolytic adenovirus (7 days) was not long enough to allow significant morphological changes to develop. Based on these factors, it is inappropriate to conclude from these studies that HSV-TK/GCV did not enhance the antitumor effects of CRADs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations